Ovarian cancer with intestinal wall invasion and hyperamylasemia: a case report - Jie, Yu; Li, Juan; Man, Chang-feng; Fan, Yu (Frontiers in Oncology, 2024)
Numerous studies have suggested a robust association between amylase and ovarian cancer. however, few amylase-producing ovarian cancers have been reported because amylase is a rare product of ovarian cancer. A case of an elderly female patient with an upper abdominal unfitness, intestinal wall along with uterine adnexal invasion, and high serum and urinary amylase is summarized in this article. The patient was initially suspected of having a gastrointestinal tumor. Initial laboratory findings showed markedly significantly raised serum and urinary amylase levels. Imaging showed invasion of the intestinal wall and uterine adnexa, and histology of the specimen taken through the abdominal wall lump and electron colonoscopy showed ovarian cancer. The patient’s blood amylase levels decreased to normal after 4 cycles of neoadjuvant chemotherapy with paclitaxel and carboplatin. Following this, she underwent interval debulking surgery, which included total hysterectomy, bilateral adnexectomy, great omentectomy, appendectomy, resection of pelvic and abdominal lesions, and partial rectal resection. Postoperative pathology and immunohistochemistry staining confirmed a diagnosis of high-grade serous ovarian cancer. This case suggests that in female patients, hyperamylasemia may indicate the presence of ovarian cancer. It is necessary to perform a multisite, multipoint histologic examination to identify the tumor’s origin in patients with multiple sites of invasion.